The type I interferon system and viruses - Garcia-Sastre, Adolfo (Henry Stewart Talks, 2018)
Introduction to the type I interferon (IFN) system, Induction of type I IFN by viruses, TLR sensors and cytoplasmic nucleic acid sensors, Inhibition of nucleic acid sensing by RNA and DNA viruses, Type I IFN signaling and its inhibition by viruses, Activities of type I IFN inducible genes and their viral inhibitors, General inhibition of host gene expression by viruses, Coordination of immune responses by type I IFN, Role of viral IFN antagonists in virus biology, Applications of viruses with debilitated interferon antagonism